2014
DOI: 10.2217/bmm.13.122
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Circulating Cytokines on Overall Survival and Disease-Free Survival in Cancer Patients

Abstract: Through their tumor-promoting and/or tumor-suppressive properties, cytokines can influence progression of cancer. We systematically reviewed the current literature on the prognostic value of the circulating cytokines IL-1α/β, IL-6, IL-8, IL-10, IL-12, TNF-α, TGF-β and IFN-γ to predict overall and disease-free survival in any type of cancer patients. PubMed was systematically searched and based on eligibility assessment using our five criteria of the Reporting Recommendations for Tumor Marker Prognostic Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 81 publications
3
12
0
Order By: Relevance
“…Elevated circulating concentrations of IL-6 have been associated with poor prognosis in several cancers including DLBCL (39, 40). IL-6 receptor signals through STAT3 increase the transcription and production of IL-6, resulting in a feed forward autocrine loop (41).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated circulating concentrations of IL-6 have been associated with poor prognosis in several cancers including DLBCL (39, 40). IL-6 receptor signals through STAT3 increase the transcription and production of IL-6, resulting in a feed forward autocrine loop (41).…”
Section: Resultsmentioning
confidence: 99%
“…Guida and colleagues (46) have reported that IL8 was unrelated with prognoses in patients with metastatic melanoma, even though the group with the highest levels of IL8 presented the lowest median OS. Other groups have reported lack of association of IL8 and prognosis (34,(47)(48)(49). Complexity of IL8 functions, technical issues, and/or characteristics of the selected patient populations may explain such discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 predicts mortality risk among various HIVuninfected populations (eg, patients with cancer [25] and healthy elderly individuals [12]). IL-6 concentrations increase with HIV infection [26], though the mechanism is unclear [27].…”
Section: Discussionmentioning
confidence: 99%